Micro‐computed tomography visualization of the vestigial alimentary canal in adult oestrid flies. Issue 3 (16th February 2018) - Martín‐Vega, D.; Garbout, A.; Ahmed, F.; Ferrer, L. M.; Lucientes, J.; Colwell, D. D.; Hall, M. J. R.
Abstract: Oestrid flies (Diptera: Oestridae) do not feed during the adult stage as they acquire all necessary nutrients during the parasitic larval stage. The adult mouthparts and digestive tract are therefore frequently vestigial; however, morphological data on the alimentary canal in adult oestrid flies are scarce and a proper visualization of this organ system within the adult body is lacking. The present work visualizes the morphology of the alimentary canal in adults of two oestrid species, Oestrus ovis L. and Hypoderma lineatum (de Villiers), with the use of non‐invasive micro‐computed tomography (micro‐CT) and compares it with the highly developed alimentary canal of the blow fly Calliphora vicina Robineau‐Desvoidy (Diptera: Calliphoridae). Both O. ovis and H. lineatum adults showed significant reductions of the cardia and the diameter of the digestive tract, an absence of the helicoidal portion of the midgut typical of other cyclorrhaphous flies, and a lack of crop and salivary glands. Given the current interest in the alimentary canal in adult dipterans in biomedical and developmental biology studies, further understanding of the morphology and development of this organ system in adult oestrids may provide valuable new insights in several areas of research. Abstract : Oestrid flies (Diptera: Oestridae) do not feed during the adult stage as they acquire all necessary nutrients during the parasitic larval stage. The vestigial alimentary canal in adult oestrid flies is visualized with the use of micro‐computed tomography and compared with the highly developed alimentary canal of adult blow flies. Adult oestrids showed significant reductions of the cardia and digestive tract, an absence of the helicoidal portion of the midgut, and a lack of crop and salivary glands.